Determinants of Financial Statement Quality: The Role of Good Governance, Technology, and Work Motivation - Rahma Danita; Nina Yusnita Yamin; Rahayu Indriasari; Phatra Anggana Djuri (Cakrawala Repositori IMWI)
Financial statements reflect the accountability and transparency of local governments to the community. This study aims to analyze the influence of Good Governance, Technology Utilization, and Work Motivation on the Quality of Financial Statements in Regional Apparatus Organizations (Organisasi Perangkat Daerah [OPD]) in Palu City. The study employed a quantitative approach involving 123 respondents consisting of OPD leaders, heads of finance sub-divisions, and operators of the Regional Government Information System (Sistem Informasi Pemerintahan Daerah [SIPD]) from 41 Regional Apparatus Organizations. Data analysis was conducted using SmartPLS with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The findings indicate that the implementation of Good Governance and Technology Utilization are key pillars that significantly enhance financial statement quality. Interestingly, Work Motivation, when examined individually, did not demonstrate a significant influence within this context. This suggests that effective systems and organizational mechanisms tend to play a more dominant role in determining financial reporting outcomes than the psychological factors of local government officials. These findings provide a new perspective for policymakers in local governments to prioritize systemic improvements and digital infrastructure development in efforts to achieve cleaner, more transparent, and more reliable financial governance.